2017
DOI: 10.3201/eid2309.161237
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase-Producing Enterobacteriaceae and Nonfermentative Bacteria, the Philippines, 2013–2016

Abstract: During 2013–2016, we isolated blaNDM- and blaVIM-harboring Enterobacteriaceae and nonfermentative bacteria from patients in the Philippines. Of 130 carbapenem-resistant isolates tested, 45 were Carba NP–positive; 43 harbored blaNDM, and 2 harbored blaVIM. Multidrug-resistant microbial pathogen surveillance and antimicrobial drug stewardship are needed to prevent further spread of New Delhi metallo-β-lactamase variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Many CPE, including E. coli and other species, possessed different types of carbapenemase. The most prevalent carbapenemase gene type was NDM (n ϭ 39; Table 2); NDM-1 and NDM-7 producers are endemic in clinical settings in the Philippines (14). We found that CPE isolates that are often found in clinical settings were also present in the environment.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Many CPE, including E. coli and other species, possessed different types of carbapenemase. The most prevalent carbapenemase gene type was NDM (n ϭ 39; Table 2); NDM-1 and NDM-7 producers are endemic in clinical settings in the Philippines (14). We found that CPE isolates that are often found in clinical settings were also present in the environment.…”
Section: Resultsmentioning
confidence: 72%
“…We found that CPE isolates that are often found in clinical settings were also present in the environment. KPC, GES, and OXA-48 producers, which have not yet been detected in clinical settings in the Philippines (14,15,17), were detected in both hospital sewage and river water. Although it is unclear whether these CPE isolates originated from humans or the natural environment, it is possible that they may spread from the natural environment to clinical settings in the future.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast to North America and Europe, NDM and other MBLs (eg, IMP, VIM), and OXA-48–type, rather than KPC, were the predominant carbapenemases in CRE in Southeast Asia [60]. A 2013–2016 study of 130 carbapenem-resistant isolates in the Philippines identified 45 (35%) carbapenemase-producing bacterial isolates with 43 (33%) testing positive for NDM and 2 (1.5%) for VIM, both of which were P. aeruginosa [61]. Surveillance reports in India and surrounding countries reveal that the most frequent carbapenemase enzymes remain NDM in Enterobacteriaceae and OXA-23 in A. baumannii [26].…”
Section: Geographic Distribution Of Carbapenem Resistance Mechanismsmentioning
confidence: 99%
“…This correlates with previous studies, in which most resistant organisms were identified as Klebsiella species. [ 20 22 23 24 ] Klebsiella species are known to be the most common carbapenemase-producing Enterobacterales in the health-care settings and have become a significant cause of morbidity and mortality in the admitted patient. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%